Cloning of Synthetic Lipase Gene from Rhizomucor miehei with Original Signal Peptide in Pichia pastoris (Indonesian Society for microbiology, 2017)
Lipases (EC 3.1.1.3) are classified as hydrolases that hydrolyze lipids. These enzymes have potential application in biotechnology and industrial process. In previous study we have cloned the synthetic Rhizomucor miehei lipase gene using the vector pUC57 in Escherichia coli DH5Î±, but only found the very low enzymes activity. This study aimed to clone Rhizomucor miehei synthetic lipase gene into Pichia pastoris expression plasmid for lipase expression with the original signal peptide. A DNA fragment with the original signal peptide had been obtained by PCR, cut by Xho I and Xba I and then ligated into pPICZÎ± A linearized with the same enzymes. The mixture of ligation, then was transformed into Escherichia coli DH5Î±. Zeocin-resistant transformants were selected and contained plasmid was analyzed by restriction enzymes analyses, PCR, and DNA sequenced. As the result, a Rhizomucor miehei lipase gene (RMlip) with the size of 1132 bp was successfully cloned to pPICZÎ± A. The recombinant plasmid with the correct DNA sequence was transformed into Pichia pastoris X33. Cultivation of recombinant P. pastoris was carried out with the addition of 1.5% methanol every day with appropriate aeration. The recombinant lipase produced by Pichia pastoris X33 containing RMlip oin its chromosomal DNA had optimal temperature and pH 30 C and 9.0, respectively.